2005
DOI: 10.1210/jc.2005-0413
|View full text |Cite
|
Sign up to set email alerts
|

EP1 Receptor-Mediated Migration of the First Trimester Human Extravillous Trophoblast: The Role of Intracellular Calcium and Calpain

Abstract: PGE2 stimulates EVT migration by signaling through EP1 receptors, increasing [Ca2+]i, and activating calpain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 64 publications
(75 reference statements)
2
54
0
Order By: Relevance
“…It is still not entirely clear which G protein(s) may be involved. The involvement of the phospholipase C (PLC)/PKC pathway in EP 1 -mediated trophoblast and osteoblast stimulation implies that EP 1 receptors may couple to G q (Nicola et al, 2005;Tang et al, 2005). Compared with other prostanoid receptor studies, the signaling properties of EP 1 receptors have received little attention.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…It is still not entirely clear which G protein(s) may be involved. The involvement of the phospholipase C (PLC)/PKC pathway in EP 1 -mediated trophoblast and osteoblast stimulation implies that EP 1 receptors may couple to G q (Nicola et al, 2005;Tang et al, 2005). Compared with other prostanoid receptor studies, the signaling properties of EP 1 receptors have received little attention.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Cluster 2 consists of EP1, FP, and TP. Although only a few studies have suggested the EP1-mediated activation of phospholipase C (PLC)/protein kinase A (PKA) (Nicola et al, 2005;Tang et al, 2005), the members of this cluster are considered to be coupled with G q a. Cluster 3 consists of the inhibitory receptor, EP3, which is coupled with G i a.…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of EP receptor agonists, we showed that EP 1 and EP 3 receptor signaling stimulates dendrite formation in melanocytes [7]. The EP 1 receptor is a low affinity receptor for PGE 2 that couples to G q to activate phospholipase C [8,9] and raises intracellular calcium. The EP 3 receptor, unlike the other PGE 2 receptors, has multiple isoforms (8 in human and 3 in mice) and couples to multiple small G-proteins, including G(i) (inhibition of adenylate cyclase), G βγ (increase in intracellular Ca +2 ) and G 13 (activation of the small G protein Rho [10]).…”
Section: Introductionmentioning
confidence: 99%